A case of spindle cell carcinoma arising in the floor of the mouth after treatment of sqamous cell carcinoma on the contralateral side of the tongue - HAGIWARA, Toshiyuki; YOSHIDA, Hiroshi; FURUYA, Yasunobu; MIYAJIMA, Youjiro (Japanese Journal of Oral and Maxillofacial Surgery, 1999)
A case of spindle cell carcinoma arising in the floor of the mouth approximately3 years after treatment for squamous cell carcinoma on the contralateral side of the tongue is presented. A 78-year-old woman was initially referred to our department because of a painful white lesion on the left lateral border of the tongue, which was diagnosed pathologically as leukoplakia. Three years 3 months later, squamous cell carcinoma developed from the lesion and was successfully treated with a combination of irradiation and surgery. Three years and 3 months after completion of treatment, a polypoid mass appeared on the right side of the floor of the mouth. Biopsy revealed atypical spindle-shaped cells showing sarcomatous differentiation associated with squamous cell carcinomatous components and very frequent mitoses, leading to a diagnosis of spindle cell carcinoma. The cancer was intraorally irradiated with a remote after loading system because the patient did not consent to surgical intervention. She died of an uncontrolled tumor 7 months after radiotherapy.